2021
DOI: 10.21608/sjas.2021.50086.1060
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by Environment Interaction and Yield Stability in Bread Wheat Cultivars under Rainfed Conditions

Abstract: The concept of stability is important for the selection of the crop cultivars and in the breeding programs. The aim of this work was to evaluate the productivity of some bread wheat cultivars under rainfed conditions of different locations in the NWCZ of Egypt. Results of the current study showed that the studied cultivars performed differently in the different environment. AMMI analysis revealed that the environment was responsible for most of the cultivars yields variation also AMMI2 bi-plot revealed that Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The results of pooled analysis of variance for stability as devised by Eberhart and Russell [11] and the AMMI model showed that variance due to genotypes and environments was significant for grain yield per plot, indicating that the performances of genotypes as well as the environments were different; the genotypes also had differential responses to the changes in the environmental conditions. Similar results were reported by Dhiwar et al [22] and Attia et al [23]. In this study, the four genotypes WH 1142, PBW 661, PBW 475 and DBW 17 had regression coefficients of 1.158, 1.13, 1.11 and 1.10 and were observed to be stable in the rich (E5) environment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of pooled analysis of variance for stability as devised by Eberhart and Russell [11] and the AMMI model showed that variance due to genotypes and environments was significant for grain yield per plot, indicating that the performances of genotypes as well as the environments were different; the genotypes also had differential responses to the changes in the environmental conditions. Similar results were reported by Dhiwar et al [22] and Attia et al [23]. In this study, the four genotypes WH 1142, PBW 661, PBW 475 and DBW 17 had regression coefficients of 1.158, 1.13, 1.11 and 1.10 and were observed to be stable in the rich (E5) environment.…”
Section: Discussionsupporting
confidence: 91%
“…According to the AMMI2 biplot, timely sown irrigated environment was determined as the most favorable environment, with the least interactive forces, and WH 1025 was highly adapted to this environment. Similarly, Attia et al [23] concluded East Barrani as most favorable environment for all cultivars according to AMMI2 bi-plot and Sakha 94 was the superior cultivar in this environment. Similar results were further confirmed by Verma and Singh [17] while analyzing the stability of wheat genotypes by AMMI in the Peninsular Zone of India.…”
Section: Discussionmentioning
confidence: 81%